“The Tragedy of the Commons”: How Individualism and Collectivism Affected the Spread of the COVID-19 Pandemic - Maaravi, Yossi; Levy, Aharon; Gur, Tamar; Confino, Dan; Segal, Sandra (Frontiers in Public Health, 2021)
Why did COVID-19 hit some countries harder than others? While this question is usually answered based on demographics (population age), health policy (quarantine), or economic factors, we argue that cultural variance across countries is just as crucial in understanding how susceptible a society is to the COVID-19 outbreak. In Study 1, we found that the more individualistic (vs. collectivistic) a country is, the more COVID-19 cases and mortalities they had. In Studies 2 and 3, we found that the more individualistic participants were, the higher the chances that they would not adhere to epidemic prevention measures. These findings are important both for understanding the spread of the pandemic and for devising optimal exit strategies from enclosures declared in many countries.